Dynamic behavior of a high-temperature printed circuit heat exchanger: Numerical modeling and experimental investigation. (5th May 2018) - Chen, Minghui; Sun, Xiaodong; Christensen, Richard N.; Skavdahl, Isaac; Utgikar, Vivek; Sabharwall, Piyush
Highlights: A dynamic model is developed for transient analysis of a zigzag-channel PCHE. Various transient scenarios of a PCHE are numerically investigated. Steady-state temperature distributions inside a PCHE are obtained. Three sets of experiments are conducted to study the dynamic behavior of a PCHE. The dynamic model is successful in predicting the experimental transient scenarios. Abstract: Printed circuit heat exchanger (PCHE) is one of the leading intermediate heat exchanger (IHX) candidates for the Very High Temperature Reactors due to its capability for high-temperature and high-pressure applications. An IHX serves to isolate the reactor primary system from electricity generation and process heat application plants, and therefore must be robust to maintain the entire system integrity during normal and off-normal conditions. Understanding the PCHE dynamic behavior is of importance in the design of a PCHE-type IHX since the dynamics of the PCHE will influence accident progression in most accident scenarios. In addition, any transient in the power conversion unit or process heat plant will propagate back to the reactor primary system via the PCHE. In this study, the dynamic behavior of a zigzag-channel PCHE, subject to helium inlet temperature variations and helium mass flow rate step changes on both the hot and cold sides, was simulated and analyzed. Three sets of transient tests were experimentally conducted in a high-temperature helium test facility to examine the dynamic performance of the PCHE and to assess the PCHE dynamic model. Comparisons of the numerical results and experimental data indicate that the numerical solutions are sufficiently accurate and that the feasibility of the dynamic model developed for predicting the steady-state and transient performance of the PCHE is confirmed.